User Interface Design for Baduy Ecotourism Website Using User Centered Design Method - Fhalosa, Muhammad Farhan; Suwawi, Dawam Dwi Jatmiko; Riskiana, Rosa Reska (Politeknik Ganesha Medan, 2023)
Baduy is one of the ecotourism destinations which offers captivating natural and cultural attractions, making it a worthy place to visit. The lack of available information in the media has piqued the author's interest in designing a visually appealing website to attract tourists. To address this issue, a user interface design will be created for the Baduy Tribe Ecotourism website using the User Centered Design (UCD) method. This method focuses on users and involves four stages, specifying the context of use, specifying requirements, designing a solution, and evaluating the design. Furthermore, to assess how well users interact with a product, usability testing will be conducted using the System Usability Scale (SUS) and Single Ease Question (SEQ). The usability testing results on the created website interface obtained a SUS score of 81 and generated 3 rating components in the SEQ method, fairly easy, easy, and very easy. Therefore, it can be concluded that the usability score falls within the category of good and is acceptable to users. Through this research, the author hopes that the user interface design for the Baduy Tribe Ecotourism website will meet users' needs, providing them with easy access to valid information and a seamless experience in discovering the natural wonders of the region.